2020
DOI: 10.1146/annurev-physiol-021119-034446
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Regulation of Renal Electrolyte Excretion: The Role of Paracrine Factors

Abstract: Many physiological processes, including most kidney-related functions, follow specific rhythms tied to a 24-h cycle. This is largely because circadian genes operate in virtually every cell type in the body. In addition, many noncanonical genes have intrinsic circadian rhythms, especially within the liver and kidney. This new level of complexity applies to the control of renal electrolyte excretion. Furthermore, there is growing evidence that paracrine and autocrine factors, especially the endothelin system, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 126 publications
1
10
0
Order By: Relevance
“…Emerging evidence continues to indicate the importance of circadian control of sodium homeostasis and BP. 14,[28][29][30] The current studies further demonstrate that the impairment of the aldosterone and ET-1 systems are more evident during the active period, a time when there is more food and water intake, and therefore, a time when precise control of sodium and water control by the kidney is more active.…”
Section: Discussionsupporting
confidence: 60%
“…Emerging evidence continues to indicate the importance of circadian control of sodium homeostasis and BP. 14,[28][29][30] The current studies further demonstrate that the impairment of the aldosterone and ET-1 systems are more evident during the active period, a time when there is more food and water intake, and therefore, a time when precise control of sodium and water control by the kidney is more active.…”
Section: Discussionsupporting
confidence: 60%
“…Use of BMAL1 knockout (KO) mouse models provides a way to gain a better understanding of the mechanism behind these human findings. Data from several mouse models have already demonstrated a link between BMAL1 and blood pressure, as summarized below and in recent review articles (45). Curtis et al (5) demonstrated that male global BMAL1 KO mice have ~10 mmHg lower blood pressure than wild-type mice.…”
Section: Introductionmentioning
confidence: 95%
“…The central circadian clock lies in the suprachiasmatic nucleus in the anterior hypothalamus and coordinates peripheral clocks, including the kidney circadian clock which, in turn, coordinate local physiologic functions with patterns of activity and/or feeding [17]. Several signals contribute to coordinate peripheral circadian rhythms, including hormone secretion (e.g., production of the melatonin hormone by the pineal gland during nighttime, circadian production of aldosterone), neuronal activity (including physical activity and feeding) and body temperature.…”
Section: Biological Rhythmsmentioning
confidence: 99%